ANATOMY OF A LOCAL ORDINANCE CAMPAIGN - ELLIS,G (Tufts Archival Research Center, 2007)
Contra Costa County Health Department outline of the anatomy of a local ordinance campaign. Provides model ordinance banning vending machine, samppling, and smoking in the workplace, restaurants, and public places. Lists benefits of focusing on local ordinances. Discusses focuses of the model. Notes shortfalls of model and lessons already learned.